New imaging techniques in AKI. Issue 6 (December 2020) - Selby, Nicholas M.; Duranteau, Jacques
Abstract : Purpose of review: Acute kidney injury (AKI) is a common complication in critically ill patients. Understanding the pathophysiology of AKI is essential to guide patient management. Imaging techniques that inform the pathogenesis of AKI in critically ill patients are urgently needed, in both research and ultimately clinical settings. Renal contrast-enhanced ultrasonography (CEUS) and multiparametric MRI appear to be the most promising imaging techniques for exploring the pathophysiological mechanisms involved in AKI. Recent findings: CEUS and MRI can be used to noninvasively and safely evaluate renal macrocirculation and microcirculation and oxygenation in critical ill patients. These techniques show that a decrease in renal blood flow, particularly cortical blood flow, may be observed in septic AKI and may contribute to its development. MRI may be a valuable method to quantify long-term renal damage after AKI that cannot currently be detected using standard clinical approaches. Summary: CEUS and multiparametric renal MRI are promising imaging techniques but more evidence is needed to show how they can first be more widely used in a research setting to test key hypotheses about the pathophysiology and recovery of AKI, and then ultimately be adopted in clinical practice to guide patient management.